Effect of rumen-protected fat on performance, carcass characteristics and beef quality of the progeny from Nellore cows fed by different planes of nutrition during gestation - Ramírez-Zamudio, Germán D.; da Cruz, Wendell F.G.; Schoonmaker, Jon P.; de Resende, Flavio D.; Siqueira, Gustavo R.; Machado Neto, Otavio R. [UNESP]; Gionbelli, Tathyane R.S.; Teixeira, Priscilla D.; Rodrigues, Liziana M.; Gionbelli, Mateus P.; Ladeira, Marcio M. (Elsevier, 2022)
The objective of this research was to evaluate the performance, carcass traits, meat quality and the expression of myogenic and lipogenic genes in muscle of steers finished with or without rumen-protected fat and born from dams that were supplemented with protein or not during mid- to late gestation. Forty-eight Nellore steers with an initial body weight (BW) of 341 ± 7.54 kg at 21 ± 0.7 months of age, were distributed in a completely randomized design using a 2 × 2 factorial arrangement with the following treatments: two offspring feedlot diets and two nutritional planes for pregnant dams. Steers born from dams of both maternal nutritional planes and reared on pasture, were allocated to individual pens for 135 days, with half of each group being fed a diet without (NFAT) or with rumen-protected fat (RPF; 6% calcium salts and 7.6% ether extract - EE). Regarding maternal nutritional planes, after 124 ± 21 days of gestation until calving, half of the grazed cows received 1 kg/cow/day protein supplement (SUPP; ∼369 g of crude protein [CP] per kg of dry matter [DM]), and the other half received only mineral salt (CTL). Steers were weighed at the beginning and at the end of the experimental period, and the weight of the feed and orts was recorded daily for performance measures. After slaughter in a commercial slaughterhouse, carcass evaluations were performed and longissimus thoracis muscle samples were collected for meat quality and gene expression analyzes using RT-qPCR. There was no interaction between the finishing diets and the maternal nutritional background for performance, carcass and meat quality traits, and gene expression of the offspring. Feeding with RPF decreased the dry matter intake, final BW, average daily gain and carcass weight (P < 0.05). Diet with RPF upregulated the MyHCI, MyHCIIx, IGFR1, COL3A1, FN1 and ACACA genes (P < 0.05) and tended to upregulate the SREBF1 (P = 0.07). Maternal supplementation did not affect feedlot performance, carcass and meat quality traits (P > 0.05). Maternal supplementation upregulated the MyHCI and CPT2 genes (P < 0.05) and tended to upregulate the FASN and ACACA genes (P < 0.10) of the offspring. In conclusion, feeding RPF to the offspring regardless of maternal nutritional background affected the performance and weight of the carcasses, as well as the expression of myogenic and fibro/lipogenic genes, without affecting the deposition of intramuscular fat, total collagen or meat tenderness.
Keywords: Fetal programming; Growth; Lipogenesis; mRNA; Myogenesis